UJI TINGKAT PATOGENITAS PENYAKIT KUDIS PADA BEBERAPA KULTIVAR UBI JALAR - Dian Muharrani Assurok; Bambang Supeno; M. Taufik Fauzi (Universitas Khairun, 2026)
This study aims to determine the pathogenicity of scab disease in several sweet potato cultivars. The method used was an experimental field trial. The experiment was designed using a randomized block design (RBD) consisting of seven treatments. The seven treatments were sweet potato cultivars, namely Tailan (T), Ase (A), Ungu (U), Cilembu (C), Lato-lato (L), Kentang (K), and Madu (M). Each treatment was replicated four times, resulting in 28 treatment units. The research results showed that plants infected with scab disease exhibited characteristic symptoms in the form of sunken brown to yellowish spots appearing on the leaves, leaf veins, petioles, and stems. Each cultivar had a different incubation period for scab disease; the Ase (A) cultivar had the longest incubation period, namely 20 days after planting (DAP), compared to the other cultivars. Disease intensity increased significantly, reaching 50–57% in the final observation at 50 HSI. Based on disease intensity data, the Ase cultivar falls into the resistant category with a disease intensity of only 3.36%, followed by the Madu cultivar, which is classified as moderately susceptible. The other five cultivars are classified as susceptible, namely the Ungu, Kentang, Cilembu, Tailan, and Lato-Lato cultivars, with disease intensity ranging from 38% to 41%.